KOMUNIKASI ANTI KEKERASAN BERBASIS ISLAM DALAM PENANGGULANGAN KEKERASAN ANTARSISWA DI SMP MUHAMMADIYAH PABUARAN BOGOR - Ellys Lestari Pambayun; Idris; Nabila Nur Uswatun Hasanah; Asmawati; Indi Fatimah Az-Zahrah (EL-ADABI : Jurnal Studi Islam, 2025)
This study explores Islamic-based nonviolent communication in addressing student-on-student violence at SMP Muhammadiyah Pabuaran, Bogor. The background of the research lies in the rising number of violence cases in school environments, prompting the need for a preventive approach rooted in Islamic values. The aim of this research is to uncover the practice of nonviolent communication from an Islamic perspective as implemented by the school in guiding students. The primary theoretical framework used is Marshall Rosenberg’s theory of nonviolent communication, examined through Islamic principles such as riyadhah (habit formation through compassion), uswah (role-modeling in brotherhood), mauizah (noble character), sermons, conflict-free interaction, and educational and Islamic disciplinary methods. This research employs a qualitative method using Edmund Husserl’s phenomenological approach to understand the subjective experiences of the involved parties. Data collection techniques include in-depth interviews and observations involving the principal, student guidance teachers, and parents. The findings indicate that a communication approach based on empathy, sincerity, and exemplary Islamic behavior effectively reduces conflict intensity and fosters more harmonious social relationships among students. The implication of this study suggests that integrating nonviolent communication with Islamic values can serve as an effective model for character education and violence prevention in schools.